Nano-zinc oxide fibers: Synthesis, characterization, adsorption of acid blue 92 dye, isotherms, thermodynamics and kinetics - Deepro Sanjid Qais; Md Nazrul Islam; Mohd Hafiz Dzarfan Othman; H.N.M. Ekramul Mahmud; Md Emran Quayum; Md Anwarul Islam; Iqbal Mohammad Ibrahim Ismail; Ahsan Habib (Emerging Contaminants, 2023)
Surface water is significantly contaminated by different dyes and pigments around the world due to rapid industrialization, especially textile/dyeing. Bangladesh's export-driven textile industry has grown dramatically over the past few decades, severely contaminating the nearby waterways. In this study, nano-zinc oxide was synthesized through precipitation method in the presence of PEG 400. SEM, XRD, and FTIR techniques were used to characterize the synthesized ZnO and revealed that it was pure, fiber-like, and essentially wurtzite. Nano-ZnO was used to remove the ionic dye acid blue 92 (AB 92) from aqueous solution in order to test its effectiveness as an adsorbent. The effects of pH, adsorbent dosage, AB 92 concentration, and contact time were investigated in order to optimize the adsorption process. According to correlation coefficients (R2) and the Redlich-Peterson model's fitting, the adsorption process followed the Freundlich isotherm at higher temperature and the Langmuir isotherm at lower temperature. The adsorption process was found to be endothermic and spontaneous. For adsorption thermodynamics, ΔH was found to be +20.32 kJmol-1, and ΔG was varied from −1.86 to −3.84 kJmol-1 as the temperature increased from 291 to 317 K. The adsorption kinetics exhibited pseudo second order. The Temkin isotherm and Elovich kinetic models suggested that the process was chemisorption. The nano-ZnO showed tremendous re-usability as an adsorbent for the removal of AB 92. The results are suggesting for designing nano-ZnO-based methods to remove organic pollutants efficiently from industrial effluents for ecological and sustainable development. The mechanism of formation of nano-ZnO fiber and adsorption of anionic dye on nano-ZnO are also explored.